2020
DOI: 10.3390/plants9040519
|View full text |Cite
|
Sign up to set email alerts
|

Resemblance and Difference of Seedling Metabolic and Transporter Gene Expression in High Tolerance Wheat and Barley Cultivars in Response to Salinity Stress

Abstract: To elucidate inter-specific similarity and difference of tolerance mechanism against salinity stress between wheat and barley, high tolerant wheat cv. Suntop and sensitive cv. Sunmate and tolerant barley cv. CM72 were hydroponically grown in a greenhouse with 100 mM NaCl. Glutathione, secondary metabolites, and genes associated with Na+ transport, defense, and detoxification were examined to discriminate the species/cultivar difference in response to salinity stress. Suntop and CM72 displayed damage to a lesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 65 publications
5
7
0
Order By: Relevance
“…Notably, the salt-pretreated group (priming + shock) was outperforming the non-pretreated group (shock only) by boosting the TaNHX1 expression levels, supporting the salt-induced priming effect approach in enhancing the salt tolerance levels in wheat plants under salt-stress conditions. The results disclosed an agreement with the previous work of Zeeshan et al (2020); as they treated the high tolerant wheat cultivar (Suntop) and the sensitive wheat cultivar (Sunmate) with 100 mM NaCl. They found that the expression level of the NHX1 gene was upregulated in Suntop (tolerant cultivar) while downregulated in Sunmate (sensitive cultivar).…”
Section: Taakt1supporting
confidence: 92%
See 1 more Smart Citation
“…Notably, the salt-pretreated group (priming + shock) was outperforming the non-pretreated group (shock only) by boosting the TaNHX1 expression levels, supporting the salt-induced priming effect approach in enhancing the salt tolerance levels in wheat plants under salt-stress conditions. The results disclosed an agreement with the previous work of Zeeshan et al (2020); as they treated the high tolerant wheat cultivar (Suntop) and the sensitive wheat cultivar (Sunmate) with 100 mM NaCl. They found that the expression level of the NHX1 gene was upregulated in Suntop (tolerant cultivar) while downregulated in Sunmate (sensitive cultivar).…”
Section: Taakt1supporting
confidence: 92%
“…Our finding showed that the expression level of the TaAKT1 gene in the salt-pretreated group (priming+shock) was higher than the non-pretreated group (shock only). This finding was in complete agreement with Zeeshan et al (2020), in which they found that the expression of the TaAKT1 gene was significantly upregulated under salinity stress in the tolerant wheat cultivar ('Suntop') while downregulated in the sensitive wheat cultivar ('Sunmate').…”
Section: Taakt1supporting
confidence: 90%
“…Highly increased activities of PAL and cinnamyl alcohol dehydrogenase (CAD), the latter being an enzyme responsible for lignin biosynthesis, in salinity-resistant barley clearly suggested their involvement in the tolerance mechanisms. In the tolerant wheat cultivar, a similar reaction was observed, but it was not as strong as that noticed in the resistant cultivar of barley [ 114 ].…”
Section: Role Of Aba In Abiotic Stressesmentioning
confidence: 57%
“…In plants, the shikimate pathway responds to differential environmental stresses (e.g., wounding, herbivore and microbial attack, or nitrogen starvation) ( Weaver and Herrmann, 1997 ). Salt stress is known to promote shikimate dehydrogenase activity in wheat ( Zeeshan et al, 2020 ), whereas chorismate synthase critically impacts barley–powdery mildew interactions ( Hu et al, 2009 ). In the current study, the expressions of shikimate dehydrogenase (aroDE), 3-phosphoshikimate 1-carboxyvinyltransferase (aroA), and chorismate synthase (aroC) were significantly up-regulated in shade-drying vs. fresh and smoke-drying vs. fresh.…”
Section: Discussionmentioning
confidence: 99%